Evaluation of the content of polyphenols, flavonoids and tannins, the antioxidant capacity, and the antimicrobial activity of different organic and aqueous fractions of stems of Retama monosperma - Benkhouili, Fatima Zahra; Moutawalli, Amina; Ouchari, Lahcen; El Fahime, Elmostafa; Benzeid, Hanane; Doukkali, Anass; Zahidi, Ahmed (Plant Science Today, 2024)
Retama monosperma is an endemic plant of the Mediterranean region that has been traditionally used in folk medicine to treat various ailments. It contains a variety of bioactive phytochemicals and exhibited several biological activities. This study aimed to assess the phytochemical screening, total phenolic, total flavonoid, and total tannin compounds, as well as the antioxidant capacity and antimicrobial activity. The phytochemical screening involved color reactions, characteristic reagents, and precipitation methods. Total phenolic, flavonoid, and tannin compounds were quantified using colorimetric methods across four fractions. Antioxidant capacity was assessed using 2,2-Diphenyl-1-picrylhydrazyl radical scavenging, ferric reducing antioxidant power, 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging, and phosphomolebdenum assay. The antimicrobial activity was evaluated through disc diffusion method and the microdilution assay. Qualitative phytochemical tests revealed the presence of flavonoids, tannins, terpenoids, alkaloids, and sterols. Quantification of total phenolic, flavonoid, and tannin compounds confirmed the richness of polyphenolic compounds in all fractions. The antioxidant capacity measurements revealed that the ethanol fractions exhibited the highest antioxidant capacity in 2,2-Diphenyl-1-picrylhydrazyl, ferric reducing antioxidant power assays, and phosphomolebdenum assay. Conversely, the aqueous fraction showed highest activity in the 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) assay. Regarding antimicrobial activity, the ethyl acetate fraction demonstrated superior efficacy against Staphylococcus aureus, and Bacillus cereus. These findings suggest that R. monosperma could serve as a valuable source of antioxidant and anti-infective phytocompounds.